Legal Protection Against Adopted Children Are Inherited Property From The Adopted Parents - Kelvin Bixby Surbakti; Hasim Purba; Maria Kaban (SEAN Institute, 2024)
Adopted children have inheritance rights similar to the inheritance rights of biological children, as stated in Staats Blad 1917 No. 38 Article 12 states that adopted children are equated with biological children born to the husband and wife who adopted them. Typically, adoption of such a child is an act that equalizes the position of the adopted child with the biological child, both in terms of care and inheritance. The problem formulation in this research is: What is the legal position of adopted children regarding the inheritance of adoptive parents based on Supreme Court Decision Number 3626 K/Pdt/2016; What are the judge's legal considerations in providing legal protection for the rights of adopted children to the inheritance of adoptive parents in Supreme Court Decision Number 3626 K/Pdt/2016; What are the implications of Supreme Court Decision Number 3626 K/Pdt/2016 for the legal protection of the inheritance rights of adopted children in Indonesia. The research method used in this research is normative juridical research, which is supported by secondary data sources, and qualitative analysis is carried out. The results of the research and discussion are that the legal position of adopted children regarding the inheritance of adoptive parents based on Decision Number 3626 K/Pdt/2016 is valid which is in accordance with the adoption decision issued by PN Number 08/Pdt.P/2003/PN Kbj. dated 28 May 2003 which determined that Rehulina Br Gurusinga was the adopted child and sole heir of Langsat Karo-Karo Gurusinga and Silo Br Sembiring. The judge's legal considerations in providing legal protection for the adopted child's rights to the inheritance of the adoptive parents in Decision Number 3626 K/Pdt/2016 by determining Rehulina br Gurusinga as the adopted child of the heir and entitled to receive the heir's property, because the judge considered the juridical aspect of where the Plaintiff was. is the adopted son and only heir of Langsat and Silo. The implications of the decision for the legal protection of the inheritance rights of adopted children in Indonesia have contributed to strengthening the legal protection of adopted children for the inheritance of their adoptive parents.